13 Minutes - Gossling, Lindsay; Farncombe, Travis; Harnisch, Karen; Vega, Paz, 1976-; Smart, Amy, 1976-; Adkins, Trace; Birch, Thora; Heche, Anne; Facinelli, Peter, 1973-; Quiver Distribution (Firm); Involving Pictures (Firm); Impact WX; et al. (United States Quiver Distribution, 2021)
As a new day begins in the small American town of Minninnewah, the residents start their day as ordinary as the next. Mother Nature, however, has other plans for them. Inhabitants have just thirteen minutes to seek shelter before the largest tornado on record ravages the town, leaving them struggling to protect their loved ones and fighting for their lives. Left to deal with the aftermath, four families must overcome their differences and find strength in each other to survive.
Title from container.
Originally released as a motion picture in 2021.
Wide screen.
Bonus features: The making of 13 minutes, story, creative process, characters, weather messaging, visual effects, extended trailer.
Music by Ariel Marx ; cinematography, Steve Mason.
Paz Vega, Amy Smart, Trace Adkins, Thora Birch, Anne Heche, Peter Facinelli.
Keywords: Tornadoes -- Drama; Survival -- Drama; Families -- Middle West -- Drama; Middle West; Disaster films; Feature films; Films-catastrophes.